The Customer Protection of Baitul Maal Wa Tamwil (BMT) on Economic Law Perspective - Wery Gusmansyah; Wahyu Abdul Jafar (Publikasi Indonesia, 2022)
This study aims to comprehensively determine the customer protection of Baitul Maal Wa Tamwil (BMT) from an economic law perspective. This study is a literature review, which uses a normative juridical approach. The data collection technique used in this research is the documentation technique. At the same time, the analytical technique used in this study is descriptive qualitative, where the author will describe the data related to Baitul Maal Wa Tamwil (BMT) in detail and then do an inductive analysis using the perspective of economic law. After conducting in-depth research, it was concluded that customers who deposit funds at Baitul Maal Wa Tamwil (BMT) do not receive guarantees from the government (because no law regulates it) if there is a crisis in BMT. Therefore, if a Baitul Maal Wa Tamwil (BMT) goes bankrupt, then based on the Civil Code (KUH Perdata), customers who deposit funds in Baitul Maal Wa Tamwil (BMT) are in the same position as concurrent creditors. As a concurrent creditor, the right to get a refund must be shared with other creditors after the Baitul Maal Wa Tamwil (BMT) assets are used to settle the obligations of the Baitul Maal Wa Tamwil (BMT) to the preferred creditor